MODEL KEPUASAN DOSEN DALAM PELAYANAN ADMINISTRASI DENGAN METODE CUSTOMER SATISFACTION INDEX - Dwi Budi Srisulistiowati; Sri Rejeki (JURNAL MITRA MANAJEMEN, 2022)
Universities need to provide the best service according to the needs and desires of lecturers. The service is good, and I hope to make it easier for lecturers, especially when reporting on the lecturer's workload. This research was conducted at the Lecturer of the Faculty of Computer Science, Bhayangkara University, Greater Jakarta. The type of research carried out in this research uses quantitative methods. The method used by data analysis technology is a method called CSI (Customer Satisfaction Index), which is used to measure the level of customer satisfaction. This research can make it easier for the Administrative Services section at the Faculty to analyze weaknesses in its services. Keywords:CSI,  Lecturer, Administrative Services